A study on the need of a specific legislation governing rights of privacy in Malaysia / Nur Syamimi Liyana Nazmi … [et al.] - Nazmi, Nur Syamimi Liyana; Mohd Nazri, Mohamad Hamdan; Wan Abu Bakar, Wan Muhamad Faisal; Che Mohd Rusof, Nursaffa Musfirah (2013)
Privacy is one of the top issues or rather controversial in our Malaysian legal branch nowadays. Based on the recent development in Malaysia the core of our rights to privacy is governed under Article 5 of the Federal Constitution. However, the rights that are protected under this Article do not cover or protect our rights of privacy as a whole. In this modern era it can be said that Right of Privacy is one of the cluster rights in order to practice the actual concept of democracy. Cluster right brings a definition of it is an ever-changing right through time and circumstances. The Malaysian Personal Data Protection Act 2010 which is also known as PDPA is related to cyber legislations and aims to regulate the processing of personal data in commercial transactions. This Act is not sufficient enough to cater the needs of the public since the horizon or scope of rights to privacy nowadays is bigger and wider than personal data of only concerns on commercial transactions only. Right to privacy is ought to adhere to everyone. In short this particular kind of right is fundamental to every human being for them to live their life freely uninterrupted by any unnecessary intervention by others in any possible means. However, it has to be in accordance with the law. There is abundance of issues pertaining to privacy and it keeps on piling up on our judiciary branch yet Malaysia still in want of a specific legislation to address to the issues at hand.